PENGELOLAAN FASILITAS ATRAKSI WISATA DI PANTAI ARTA INDAH KABUPATEN PADANG PARIAMAN - Hidayatullah, Riyan; Yuliana, Yuliana; Ferdian, Feri (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research aimed to describe the management (planning, organizing, directing, and supervising) of tourist attractions at Arta Indah Beach which includes: (a) children game facilities, (b) water recreation facilities and (c) fishing leisure facilities. This type of research is descriptive qualitative data. The type of data used is primary data and secondary data. Technique of collecting data is done by using observation method, interview, and documentation that involve, that is: management of tourist object and society around tourist object. Qualitative data analysis techniques covering three activities: data reduction, data presentation, and conclusion. Based on the research results found some things related to the management of tourist attraction facilities in Arta Indah Beach are: 1) the management of children's game facilities from the organizing is good, the supervision has been, but the children's game plan planning which includes game buayan Kaliang and game throwing bracelet still less . The planning of child play facilities organized by managers is still general and not too detailed. Planning of children game facilities at Arta Indah Beach Tourism Objects exist, only for sustainability and yet leads to the development of attraction facilities in tourism object, 2) management of water recreation facility that is good organizing benen rent, guidance already, but supervision of water recreation facility that is leasing Benen is still not good. The supervision of the benen rental facility at Arta Indah Beach is only the general standards, to measure the achievement of the objectives set in the rental facility of the benen; 3) the management of fishing facilities ie the boat facility of the planning is good, the guidance already exists, but for the organizational structure and The division of duties from the management of the canoe facilities does not exist, just waiting for the instructions from the Management Board.Keywords: Management, Facilities, Tourist Attractions